GIS and Water Quality Index Based to Assess Spring Water Quality, A Case Study of Bani Kinanah District, Irbid, Northwestern Jordan - Mohammad A. Khawajah; Ahmad A Al-Taani; Abeer I Al-Zoubi; Abeer A Al-Hamad (Indonesian Journal on Geoscience, 2023)
Springs in northwestern Jordan are significant sources of freshwater for local communities. The reliance on springs to fulfill the growing demands for water has been intensified in the past decade, following the decline in rainwater due to climate change. Thirty water samples were collected from springs located in Bani Kinanah District, northwest Jordan, and tested for various water quality parameters, including pH, EC, TDS, Na+, Ca+2, Mg+2, K+, Cl-, F-, SO4-2, NO3-, TH, TA, Fe, Mn, Pb, and Zn. The results show that most water quality variables fall within the acceptable limits for drinking water set by the World Health Organization (WHO) and the Jordanian standards, except for a few indicators. The chemistry of spring water is mainly governed by rock weathering, with dominant Ca-Mg-HCO3 type of water. The spatial distribution of TDS in spring water shows relatively high levels in springs located in northern and northeastern areas. Based on the water quality index (WQI), twenty-six springs are either of excellent or good water quality, and are suitable for drinking purposes. Whereas four springs (Kharja, Malka, EL Za'agah, and Sa'ed) have poor quality and designated for irrigation and industrial usage. This may be due to its proximity to residential areas, as noted in the field observation. Evaluation of the spring water suitability for irrigation shows that most springs are of excellent to good quality, and only a few springs fall under the category of good to permissible for irrigation. Keywords: Water Quality Index (WQI), Geographic Information System (GIS), spring water, Bani Kinanah